Exercise prescription in weight training: A needs analysis - Kraemer, W. J. (Strength and Conditioning Journal, 1983)
The development of optimal weight training programs requires a needs analysis. As the term implies, a needs analysis is a logical method for the coach to use in deciding what work the athlete should do. By fully evaluating the total strength and conditioning needs of the athletes, the strength and conditioning coach can better help the athlete achieve improved sport performance through optimal weight training exercise prescription. First, a biomechanical and metabolic analysis of the sport is needed. Each sport (position) has specific needs that must be addressed by the strength and conditioning coach. First Biomechanical Specificity, or "what are the muscles used in the sport?" and, "what are the primary angles in which these muscles are used?" Because of the vast number of exercises to choose from, it is important that the coach be able to identify those movements and muscles which play a prime role in the sport. Next, the coach should determine the metabolic profile of the sport. Metabolic Specificity in training is vital to eventual success. One of the easiest ways to do this is to use the duration of the activity to determine the metabolic profile.